Opinion of veterinary students towards establishment of private veterinary clinics - V. Jagadeeswary; B. Sudhakar Rao; C. Subhash Chandra Boss (Journal of Agricultural Extension Management, 2025)
In India, the problem of unemployment among veterinary graduates has been steadily increasing over the last few years due to the establishment of more number of Agricultural and Veterinary Universities and professional colleges. Though the number of .state run veterinary institutions increased from about 2000 in 1951 to over 54,000 by the end of 1997-98 (Basic Animal Husbandry Statistics, 2002) they are not in a position to accommodate all the veterinary graduates because of financial constraints. This has resulted in a wide gap between the available veterinary graduates and the jobs available, and this gap has been on increasing over the years. To solve this problem, fresh graduates from the universities and colleges could be potentially employed through establishment of private clinics. In this direction, the Government of India, Ministry of Agriculture and National Bank for Agriculture and Rural Development have started a scheme called "Agri-clinics and .A.gri-business11 centres scheme with a view to provide training to the graduates in Agri-business and later to support them financially for establishing veterinary clinics. In this context, empirical evidence on the opinion of veterinary graduates • on establishment of private veterinary clinics would unearth the ground reality, as they are the personnel who would be engaged in providing services to the farmers and hence this study was undertaken